1999
DOI: 10.1083/jcb.144.5.915
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Membrane-associated Procaspase-3 Is Regulated by Bcl-2

Abstract: The mechanism by which membrane-bound Bcl-2 inhibits the activation of cytoplasmic procaspases is unknown. Here we characterize an intracellular, membrane-associated form of procaspase-3 whose activation is controlled by Bcl-2. Heavy membranes isolated from control cells contained a spontaneously activatable caspase-3 zymogen. In contrast, in Bcl-2 overexpressing cells, although the caspase-3 zymogen was still associated with heavy membranes, its spontaneous activation was blocked. However, Bcl-2 expression ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 56 publications
4
38
0
Order By: Relevance
“…Thus, COX-2 expression may interfere with the maintenance of Bcl-2 and Bcl-x L patterns of expression in WT livers, perhaps making these livers more susceptible to apoptosis. Bcl-2 controls cytoplasmic events in part by blocking the activation of membrane-associated procaspases (50). Indeed, in our settings, caspase-3 activation was significantly reduced in COX-2 Ϫ/Ϫ livers as compared with control littermates after I/R injury, and it was accompanied by a reduced number of TUNEL-positive cells observed in the COX-2-deficient livers.…”
Section: Discussionmentioning
confidence: 53%
“…Thus, COX-2 expression may interfere with the maintenance of Bcl-2 and Bcl-x L patterns of expression in WT livers, perhaps making these livers more susceptible to apoptosis. Bcl-2 controls cytoplasmic events in part by blocking the activation of membrane-associated procaspases (50). Indeed, in our settings, caspase-3 activation was significantly reduced in COX-2 Ϫ/Ϫ livers as compared with control littermates after I/R injury, and it was accompanied by a reduced number of TUNEL-positive cells observed in the COX-2-deficient livers.…”
Section: Discussionmentioning
confidence: 53%
“…30 ± 34 It is believed that these zymogens are released into the cytosol prior to their activation by Cytochrome c and Apaf-1. 30 ± 34 The regulation of the membraneassociated caspase-3 was, however, distinct from that of cytosolic caspase-3; for example, membrane-associated caspase-3 was regulated by Bcl-2 but was insensitive to exogenous Cytochrome c whereas cytoplasmic caspase-3 was directly activated by Cytochrome c. 31 We have also seen a decrease in procaspases-9, -7 and -3 in the HM membrane fraction following exposure to cDDP but a decrease in proform was associated with an increase in processed forms, suggesting that processing of caspases may in fact take place in the membrane fraction. This was substantiated by the increase in DEVD cleavage activity in the HM fraction as well as cleavage of the substrate PKCd.…”
Section: Discussionmentioning
confidence: 99%
“…They documented a diffuse cytosolic staining and a punctate cytosolic staining for caspase-3 expression by IHS using an antibody that recognizes the "uncleaved" form and demonstrated that patients with the diffuse-staining tumor had a significantly poorer prognosis as compared with those with the punctate-staining tumor. Recent studies have revealed that "uncleaved" caspase-3 is present in mitochondria as well as in cytoplasm [27][28][29], and Donoghue et al [18] speculated that punctate staining was seen when caspase-3 was localized in mitochondria. In the present study, we could not distinguish different caspase-3 staining patterns.…”
Section: Discussionmentioning
confidence: 99%